Public Budgeting in Context : Structure, Law, Reform and Results. - Willoughby, Katherine G. (Wiley, 2014)
Public budgeting structure, process, legal framework and policy with examples from industrialized and developing countries Public Budgeting in Context examines budgeting at all levels of U.S. government-federal, state, and local-and in a sample of governments around the world. The book assesses the context of public budgeting in these governments, especially the legal foundations for its practice and how the process and final budgets are impacted by governance structures, laws, various budget actors and different branches of government. The author presents focused attention on the influences o.